Status of Novel Coronavirus Disease 2019 (COVID-19) and Animal Production - Defo Deeh, Patrick Brice; Kayri, Veysi; Orhan, Cemal; Sahin, Kazim (Frontiers in Veterinary Science, 2020)
In December 2019, a severe acute respiratory syndrome coronavirus -2 (SARS-CoV-2) that caused severe disease clusters was first reported in Wuhan, the capital of China's Hubei province. This viral disease, which is reported to originate from a seafood market where wild animals are illegally sold, has been transmitted among humans worldwide through close contact. Given the growing number of infected people worldwide and the disastrous consequences in all aspects of life, COVID-19 is a serious public health issue that requires special attention. In some countries, the epidemic curve of infection which was in the plateau phase or decreasing phase during the lockdown period increases day by day since the reopening, indicating the second phase of contamination. Therefore, the preventive measures recommended by the World Health Organization (WHO) must be respected to stop the spread of the disease. The international crisis due to the COVID-19 pandemic negatively affects many sectors, including animal production and its related industries. Indeed, with the cessation of imports and exports between countries, it is not possible to provide feeds that are considered as basic raw materials in livestock raising. This situation impairs animal movements, decreases production inputs availability, and negatively affects the economy. The sustainability of animal production is also affected by a shortage of workers due to the lockdown/curfew, the strong decrease in the purchasing power of the consumer, and the intensification of health care tasks. To prevent contamination of animal products and the spread of the disease with food, the U.S. Centers for Disease Control and Prevention (CDC) recommends frequent disinfection of food and human contact surfaces at production sites using an appropriate antiseptic. The purpose of this review article is to describe the current status of COVID-19 and investigate its effects on animal production. We propose potential approaches to keep animal products processing units and staff safe from SARS-CoV-2 infection and some strategies to improve animal production quantity and economy